POPULATING INSTITUTIONAL REPOSITORY: FACULTY’S CONTRIBUTION AND ROLES OF LIBRARIANS - Abrizah, A. (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2010)
Institutional Repositories (IRs) are predicated on contributions by members of a university community, particularly faculty members. In fact, faculty contribution are crucial to the success of an IR even though several studies have found low rates of faculty submission. In order to address low submission rates and provide an (IR) that will preserve and disseminate research materials, a research-intensive university in Malaysia conducted a web-based survey to investigate faculty’s use of open access repositories, advocacy undertaken, and attitudes toward the contents of IR. Responses were received from 131 academics from 14 faculties, institutes and centers at the university. Research questions posed were, among others “Are faculty members aware of Institutional Repositories? What is their opinion about IRs? Are they willing to contribute in IR, if they are given a chance? One half of the respondents mentioned allowing, or even encouraging, the deposit of theses and dissertations. Findings indicated that, as users the academics wanted to find many more types of material in the repository and as authors, they were willing to deposit, particularly to disseminate their work and receive feedback, and also to support the principle of open access. The greatest deterrents to contributing were the risk of being unable to publish elsewhere later, the ownership of copyright, and plagiarism. However, the faculties in this study are poorly informed on institutional repositories, with almost two-thirds not knowing if their institution has one. This low level of awareness may be due to the university library managing its repository, using librarians to collect and deposit materials on behalf of faculty members. The implication is that the librarians has an important role to play with regard to the relationship with self-archiving authors, which is the key characteristic of IRs. The paper has identified the following roles for librarians in an IR environment: (a) Understanding the IR software used; (b) Publicity and advocacy of IR; (c) Establishing an institutional mandate; (d) Educating faculty regarding self-archiving issues; (e) Submission review for content and metadata; and (f) Training of authors. Based on methodical IR development informed by best practices in the Open Access community, the findings from this study have been used for repository design customizations and functionality enhancements that complement the needs, interests and concerns of the faculty. An outcome of the research is an institutional repository (IR) to support for a new pattern for scholarly communication, apart from servicing the university’s research output.